Satisfaction With the Collaboration Between Families and Schools – The Parent’s View - Paccaud, Ariane; Keller, Roger; Luder, Reto; Pastore, Giuliana; Kunz, André (Frontiers in Education, 2021)
Families and schools are two of the central living environments of children. Their collaboration is therefore seen as an important factor in education, having a high impact on learning outcomes, motivation and children’s health. Nevertheless, current research also shows potential tensions in the educational partnership of families and schools, as different opinions and expectations about goals, competences and roles in education can result in conflicts. Based on a nationwide survey of Swiss parents who assessed the school situation of their children (N=1275), this study examined parent's experiences, needs and expectations regarding collaboration with schools, with a focus on important issues such as involvement in educational decisions, inclusion, and health. Results show a generally high level of satisfaction among parents, which is particularly related to the emotional well-being of their children at school, the quality of collaboration, and the trust in schools and teachers, both for parents of children with and without SEN. Nevertheless, involvement in educational decisions is perceived as rather marginal. Furthermore, the results indicate that parents of children with SEN are less confident about their children's future. They are also less optimistic about their children's academic self-concept and generally more dissatisfied with their children's school. Parents' attitudes towards inclusion showed a wide range of opinions: on the one hand, inclusion is seen positively in terms of developing students' social skills or promoting a more inclusive society. On the other hand, however, the resources of the school and the skills of the teachers were sometimes considered as insufficient. Our findings provide important insights regarding the further development of the educational partnership between schools and families. Good collaboration between schools and families can create an environment that promotes students' emotional well-being as well as their academic skills. The positive impact of this partnership has been demonstrated in numerous studies and contributes to the implementation of an inclusive healthy school.